Developing Science Concepts of Students with Visual Impairment through ADDIE Instructional Design Model versus Conventional Teaching - Qaisar, Sana; Bashir, Rukhsana; Ashraf, Samina (Annals of Human and Social Sciences, 2023)
The objectives of the study was to develop science concepts of students with visual impairment (SWVI) through ADDIE instructional design model versus conventional teaching. Experimental study under quantitative approach followed a quasi-experimental research design was adopted to collect data from 20 students. 10 students out of 20 were randomly selected for treatment/experimental group while 10 students were randomly selected as control group from (Govt. Sunrise Institute for the Blind, Ravi Road, Lahore). The multi-stage random sampling technique was followed to get the sample of 20 students from 37 students at elementary level. In the experimental group, about 10 students received intervention using ADDIE instructional design model, while the control group received conventional teaching. Pre-tests were administered to both groups and after a twelve-week intervention, post-tests were conducted. Independent t-tests and paired sample t-tests were used to analyse the results.The findings indicatethat learning enhance in abstract concepts of science to SWVI at grade 6th by using instructional package as compare to conventional teaching. It was recommended that to teach logical reasoning and analyzing skills among students with visual impairment, teachers need to tailor instructional strategies to meet the unique needs of visually impaired students in science education.